The contribution of the Facebook social network in supporting and mediating biology classes of the First Year in Polytechnic Education by Basic Education Leopoldo Ost School - Ramiro, Adriane Ziegler; Medeiros, Liziany Muller; Lima, Andréia Lucimar Silva de; Silva, Juliana Santos da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
his article aims to evaluate the contribution of the Facebook Social Network in supporting and mediating biology classes of the First Year in Polytechnic Education by Basic Education Leopoldo Ost School. The college is located in the municipality of Santo Cristo -RS. The participation of students in a group logging Biology is analyzed, through the use of Technologies informing and communicating with each other and building knowledge collectively. The study was conducted from March to June 2014, using action research and qualitative observation of the interaction and participation of students in the group and evaluation questions. The social network (Facebook) has attracted the students to participation and information sharing, motivating and awakening them to their studies. In fact, it is noticed that the Facebook Social Network presents great potential for mediation of teaching learning process, both in support and in building new knowledge in Biology.